Correlation of the clinical severity of atopic dermatitis with ocular comorbidities. Issue 5 (30th June 2020) - Numata, Takafumi; Ito, Tomonobu; Yamamoto, Kaori; Kawakami, Setsuko; Wakabayashi, Yoshihiro; Goto, Hiroshi; Tsuboi, Ryoji; Okubo, Yukari
Abstract : We compared the incidence of various ocular comorbidities and the clinical severity of AD using the Eczema Area and Severity Index (EASI) score.